If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 35 = -7 + -35 Reorder the terms: 35 + 7x = -7 + -35 Combine like terms: -7 + -35 = -42 35 + 7x = -42 Solving 35 + 7x = -42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 7x = -42 + -35 Combine like terms: 35 + -35 = 0 0 + 7x = -42 + -35 7x = -42 + -35 Combine like terms: -42 + -35 = -77 7x = -77 Divide each side by '7'. x = -11 Simplifying x = -11
| 0=79000C-(1+C^2)(4.9)(88.96396)-183 | | (3a-b)(3a-b)= | | 7.5=9.3-0.2x | | 6-9x=7x-10x-30 | | 10=12-2z | | 0.01x+0.10(100-x)=0.41x | | 12=2(5x+6) | | 10y=2x+3zy+1 | | -5r-7=8 | | -(8x-2)=-(2x-2) | | 2y+3y-18=-83 | | 1=z+3 | | 2(lnx)*2-9lnx-18=0 | | 40+4x=28 | | 5+15=25 | | -3(8n-3)=-33-4n | | 2z-1=2z-5 | | 2(1+8x)=-110 | | 2x+40=0.18 | | -0.10(41)+0.85x=0.05(x-18) | | -4(8+4x)-8=-40-8x | | -(7x-3)+4x-5=-2 | | 4(3x+2)-x=x | | 6(3+w)+3w+5(4w+2)= | | 0=2205C-(1+C^2)(4.9)(2.48)-183 | | 4(3x+2)-x=x+1 | | 3x+25=3+7x-6 | | 5p=2p+4 | | 10=12-22 | | 4(3x+2)-x=x-3 | | 3p-2=-7 | | -0.2k+2.8k=0.48 |